2012
DOI: 10.1016/s1474-4422(11)70305-2
|View full text |Cite
|
Sign up to set email alerts
|

Autologous mesenchymal stem cells for the treatment of secondary progressive multiple sclerosis: an open-label phase 2a proof-of-concept study

Abstract: SummaryBackgroundMore than half of patients with multiple sclerosis have progressive disease characterised by accumulating disability. The absence of treatments for progressive multiple sclerosis represents a major unmet clinical need. On the basis of evidence that mesenchymal stem cells have a beneficial effect in acute and chronic animal models of multiple sclerosis, we aimed to assess the safety and efficacy of these cells as a potential neuroprotective treatment for secondary progressive multiple sclerosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
336
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 555 publications
(357 citation statements)
references
References 32 publications
(27 reference statements)
4
336
0
5
Order By: Relevance
“…T1 hypointense lesion volume decreased after treatment and magnetization transfer ratio increased, but these changes were no longer statistically significant. These findings could provide indirect support for this idea that MSC can promote re-myelination and can have a neuroprotective effect [49].…”
Section: Mscmentioning
confidence: 89%
“…T1 hypointense lesion volume decreased after treatment and magnetization transfer ratio increased, but these changes were no longer statistically significant. These findings could provide indirect support for this idea that MSC can promote re-myelination and can have a neuroprotective effect [49].…”
Section: Mscmentioning
confidence: 89%
“…At present, in vitro and in vivo studies have demonstrated that MSCs can differentiate beyond mesodermal lineages and into endodermal and ectodermal lineages [6][7][8][9]. In addition, isolation of MSCs from bone marrow is a well-established method accredited with standards for good manufacturing practice and is currently used in clinical trials [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…MSCs were isolated from bone marrow aspirates from the iliac crest of healthy volunteer adult donors (age [37][38][39][40]. The Hospital Ethics Committee approved cell harvesting of UCs and informed consent was given by the parents.…”
Section: Ethicsmentioning
confidence: 99%
“…A few phase I studies have shown that these cells are safe 7 , and researchers are now looking for signs of efficacy in larger phase II trials. Freedman, for example, is collaborating with colleagues to enrol 40 patients with either relapsing-remitting or secondary progressive MS into a Canadian trial called MESCAMS.…”
Section: Divided Opinionmentioning
confidence: 99%